Designing a positioning system for finding things and people indoors. - Werb, J.
Despite extraordinary advances in Global Positioning System (GPS) technology, millions of square meters of indoor space are out of reach of Navstar satellites. Their signals, originating high above the Earth, are not designed to penetrate most construction materials, and no amount of technical wizardry is likely to help. So the greater part of the world's commerce, being conducted indoors, cannot be followed by GPS satellites. Here, the authors describe how tracking people and assets indoors has now moved from the realm of science fiction to reality, thanks to a radiofrequency identification technique now being introduced to the market
Keywords: 3D-iD tracking system; Asset tracking; Implementation; Indoor space; Installation; Local positioning system; Personnel tracking; Radiofrequency identification technique; Software platform